Adenomyomatosis of the Common Bile Duct and Ampulla of Vater - Gouveia,Catarina (2021)
Abstract: Adenomyomatosis is a rare benign lesion that has been observed in different sites throughout the gastrointestinal tract, most frequently in the gallbladder. Few cases have been described in the stomach, small bowel, bile ducts, and ampullary region. Adenomyomas of the vaterian system (ampulla and common bile duct) have important clinical consequences, since the majority of these lesions presente with biliary tract obstruction and mimic malignant behavior. As a consequence, considering the diagnostic difficulty of these lesions, patients are often treated with extensive surgery (pancreaticoduodenectomy). We report 2 cases of adenomyomatosis: one of the ampulla of Vater and the other of the common bile duct, as well as a review of reported cases in the literature. Both of our patients presented with epigastralgia and had laboratory or endoscopic evidence of biliary obstruction. Both patients underwent endoscopic ultrasound, one of them with fine-needle aspiration; however, it was not possible to exclude the possibility of cancer. The diagnosis of adenomyoma was only confirmed by the surgical specimen after pancreaticoduodenectomy.